A Spot on the Abdomen. Issue 3 (May 2016) - Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. In this modality, there is transfer of patient medical information electronically (including history and visual data) obtained in one location to a provider who is in another location (Roman & Jacob, 2015). The construct of the TeleDermViewPoint column is such that cases are presented in a standardized teledermatology reader format reflective of an actual teledermatology report. This is a case of a spot on the abdomen.